202 Evaluating Finishing Performance of Cattle Fed High-Moisture Corn: Steam-Flaked Corn Blends with Modified Distillers Grains. (12th April 2022) - Troyer, Braden; Carlson, Zac; McPhillips, Levi J; Watson, Andrea K; MacDonald, Jim C; Erickson, Galen E
Abstract: Steam-flaked corn (SFC) and high-moisture corn (HMC) offer benefits to the cattle feeding industry including improvement of feed efficiency (G:F) and a guarantee of grain supply, respectively. Popularity of SFC in the Midwest is increasing. A study compared finishing cattle performance when fed HMC, SFC, or blends. The objective was to determine the optimum inclusion of HMC:SFC ratio with or without modified distillers grains (MDGS) included at 20% of the diet. This study utilized 120 yearling steers (352 kg; SD=7.1 kg) individually fed using the Calan gate system in a completely randomized design with cattle stratified by body weight (BW). Treatments included: 100% HMC, 50:50 blend HMC:SFC, or 100% SFC fed with and without 20% MDGS. Additionally, a 25:75 blend and a 75:25 blend of HMC:SFC was fed with MDGS only for a total of 8 treatments (DM basis). Cattle were on feed 140 d with 3-d initial BW and 1 d final BW and carcass weight and characteristics. Animal was the experimental unit with 15 replications per treatment. A tendency for an interaction ( P = 0.11) was observed for ADG between distillers inclusion and ratio of HMC:SFC. Cattle fed diets with no distillers grains had improved ADG when fed a blend of HMC:SFC ( P = 0.07), but gain was not impacted ( P = 0.59) as SFC replaced HMC in diets with 20% MDGS. Feeding MDGS increased carcass weight, ADG, intake, and fat thickness compared with control diets ( P ≤ 0.04). For diets containing 5 ratios of HMC:SFC with 20% MDGS, feeding greater inclusions of SFC had no impact on intake or ADG ( P ≥ 0.31) but tended to linearly improve G:F ( P = 0.09). Overall, including MDGS in HMC, SFC, or blended diets increased carcass weight, ADG, and intake and G:F was improved as SFC increased in diets with MDGS.